Prmary adenomyoepithelioma of the skin-a variant of apocrine mixed tumor? - Elisabeth Reidl; Geoffrey J. Gottlieb (Mattioli1885, 2012)
Analogous to adenomyoepitheliomas of the breast, cutaneous adenomyoepithelioma is composed of two components, one being myoepithelial, the other ductal epithelial, and it lies in the spectrum of neoplasms having a "pure" myoepithelioma at one end and a mixed apocrine tumor at the other. We present the case of a 53-year-old woman with a 3 cm nodular lesion on her left forearm that had been present for many years. Histopathologic examination revealed a large lobulated neoplasm surrounded by a compressed fibrous pseudocapsule. Most of the cells that constituted the lesion displayed myoepithelial differentiation arranged in solid sheets, cords, and solitary units. Glandular and ductal structures with features of apocrine differentiation composed the second part of the neoplasm. The myoepithelial cellular component of the neoplasm stained for S100 protein and was negative for cytokeratin and carcinoembryonic antigen (CEA). Based on findings by conventional microscopy and immunohistochemistry, the neoplasm was classified as primary adenomyoepithelioma of the skin.